System Dynamic Models As A Basis Strategy Development of Tin Ore Production Optimization Case Study: Indonesia Tin Mining Company - Sujoko, .; Tjakraatmadja, Jann Hidajat (Jurnal Aplikasi Manajemen, 2013)
This study is a case study on a tin mining company in Indonesia. The core business of this company is Tin Business. Amount of tin ore production is key success factor for this business. Tin ore production system is a fairly complex system, always changing along with the changing times and the environment change either internal or external environment. This system characterized by dynamically. Thus tin ore production system is dynamic system. Referring to that in this study used system dynamic model as a tool to evaluate and develop strategy to improve optimization of tin ore production. Tin ore production systems consist of two types, there are legal mining and illegal mining. Tin ore production systems are affected by some reinforcing systems and some balancing systems. Legal mining production System characterized by limits to growth, while the illegal mining production system characterized by tragedy of common. The main factors affecting the company performance are the tin price and tin resources. Both of these factors are difficult to control by the company. Thus, strategy development for optimizing tin ore production can be performed on other variables that can be controlled by the company. Company performance in the future depend on level of company ability in optimize production. In this study will be built a model using system dynamic method. The target is to finding important factors in the tin ore production system and how relation between the factors, then it's can be find of strategy formulation to production optimization. With this effort are to sustainability and growth of the company can be assured.